Digitalisasi Keuangan dan Persepsi Penggunaan GrabFood-OVO: Dampaknya terhadap Kinerja Keuangan UMKM Makanan di Era Platform Economy - Wita Ramadhanti; Triani Arofah; Oman Rusmana (Jurnal Riset Akuntansi Soedirman, 2026)
The rapid growth of digital platforms in Indonesia has transformed how micro, small, and medium enterprises (MSMEs) conduct financial transactions. This study examines the level of financial digitalization adoption, perceptions of GrabFood and OVO platform use, and their association with the financial performance of food-sector MSMEs partnering with GrabFood in Banyumas Regency. Using a descriptive-quantitative approach with a survey of 34 respondents, this study analyses three constructs: financial digitalization (7 items), perception of GrabFood–OVO use (9 items), and financial performance (7 items). Results indicate that financial digitalization is perceived at a high level (mean = 4.08), followed by GrabFood–OVO use (mean = 3.88), while financial performance remains at a moderate level (mean = 3.45). These findings suggest that although MSMEs have broadly adopted digital financial tools and perceive them positively, the translation into measurable financial outcomes — particularly revenue growth and market expansion — remains incomplete. This study contributes empirical evidence to the platform economy literature and offers practical implications for MSME development policies in Indonesia.